1996
DOI: 10.1897/1551-5028(1996)015<0092:tavdot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Vertical Distribution of Total Ammonia Nitrogen and Un-Ionized Ammonia Nitrogen in Sediment Pore Water From the Upper Mississippi River

Abstract: Abstract-We examined the temporal and vertical distribution of total ammonia nitrogen (TAN) and un-ionized ammonia nitrogen (NH 3 -N) in sediment pore water and compared the temporal patterns of TAN and NH 3 -N concentrations in overlying surface water with those in pore water. Pore water was obtained by core extraction and subsequent centrifugation. We measured TAN concentrations and calculated NH 3 -N concentrations from February through October 1993 at four sites in Pool 8, upper Mississippi River, at depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 0 publications
1
27
2
Order By: Relevance
“…As a type of cyprinid, M. amblycephala obtained from Lake Taihu, which is a fresh water lake with frequently and severe water bloom in China, showed a relatively low MCs content (1.7 ng g −1 , wet weight) in muscle . According to the method of Liang et al , the estimated dietary intake values of MCs in these M. amblycephala muscles (0.0085 µg kg −1 body weight per day) were much lower than 0.04 µg kg −1 body weight per day, which is the tolerable daily intake of MC‐LR suggested by the World Health Organization . Additionally, a previous study reported that M. amblycephala muscle was safe for human consumption, although fish were fed diet containing up to 25.32% cyanobacteria powder for 12 weeks.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…As a type of cyprinid, M. amblycephala obtained from Lake Taihu, which is a fresh water lake with frequently and severe water bloom in China, showed a relatively low MCs content (1.7 ng g −1 , wet weight) in muscle . According to the method of Liang et al , the estimated dietary intake values of MCs in these M. amblycephala muscles (0.0085 µg kg −1 body weight per day) were much lower than 0.04 µg kg −1 body weight per day, which is the tolerable daily intake of MC‐LR suggested by the World Health Organization . Additionally, a previous study reported that M. amblycephala muscle was safe for human consumption, although fish were fed diet containing up to 25.32% cyanobacteria powder for 12 weeks.…”
Section: Discussionmentioning
confidence: 81%
“…According to the analysis of MCs content, MCs intake in the non‐dietary cyanobacteria groups (CON and NH 3 ) and dietary cyanobacteria groups (MCs and NH 3 + MCs) was 0 and 8.46 mg kg −1 body weight per day, respectively. Based on the toxin levels in a field during degradation of Microcystis blooms, the concentration of un‐ionized ammonia in the water of the non‐ammonia treatment groups (CON and MCs) and ammonia treatment groups (NH 3 and NH 3 + MCs) was adjusted to 0 and 0.12 mg L −1 , respectively. The concentration of un‐ionized ammonia was adjusted by dissolving ammonium chloride in de‐chlorinated water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enrichment is known to generate an increase in the levels of NO 3 -N in the interstitial water (Hansen et al, 1998). Due to their toxicity, NO 3 -N at high concentrations are considered to be key factors in the succession of benthic macroinvertebrates (Wilson et al, 1995;Frazier et al, 1996;Sparks and Sandusky, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have monitored concentrations of contaminants in fish (Hora 1984;Wiener et al 1984), invertebrates (Beauvais et al 1995;Steingraeber and Wiener 1995), sediments (Bailey and Rada 1984;Wiener et al 1984;Rada et al 1990;Frazier et al 1996;Ingersoll et al 1998), or a combination of the three (Peddicord et al 1980;Boyer 1984) in select pools in the UMR. However, no information was available on contaminant concentrations and toxicity in sediment samples throughout the entire pool system of the UMR.…”
mentioning
confidence: 99%